Determinan Penyaluran Kredit UMKM PT. Bank Maluku Malut - Samie Lambert Jacobs; Maximiliane L. C. Hukom (Univiversitas Dr. Djar Wattiheluw, 2020)
This study aims to analyze the influence Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Return on Assets (ROA) against lending UMKM banking on PT Maluku Regional Development Bank Maluku, Maluku Utara. The object of this research is a banking company BPDM, Maluku Utara period 2015 – 2019. Hypothesis testing is tested empirically using Multiple Linear Regression and Classical Assumption Test. Based on the analysis that has been done, the results show that the ratio is partial CAR, NPL and ROA has a significant positive effect on lending UMKM at Maluku Regional Development Bank Maluku, Maluku Utara period 2015 – 2019. This is evidenced by a significant level CAR, NPL and ROA that is smaller than 0,05 so that from the results of processing SPSS obtained the magnitude of R sguare (r2) is 0.991. This figure means that the effect of the three independent variables used in this study, jointly (simultaneously) has an effect on lending UMKM at Maluku Regional Development Bank Maluku, Maluku Utara is 99,1%. The remaining 08.0% was influenced by other factors. In other words, variable CAR, NPL and ROA is 99.1%, while 09.0% is caused by other variables outside this model.